Clinical relevance of antigen spreading pattern induced by CHP-MAGE-A4 cancer vaccination. (May 2016) - Miyauchi, Kengo; Tsuchikawa, Takahiro; Wada, Masataka; Abiko, Takehiro; Kyogoku, Noriaki; Shichinohe, Toshiaki; Miyahara, Yoshihiro; Kageyama, Shinichi; Ikeda, Hiroaki; Shiku, Hiroshi; Hirano, Satoshi
Aim: To investigate the antigen spreading pattern in the CHP-MAGE-A4-vaccinated patients and analyze the clinical relevance of antigen spreading pattern as a surrogate marker of patient survival.Materials & methods: 12 patients who had been injected with 300 μg of CHP-MAGE-A4 and 0.5 Klinische Einheit of OK-432 in more than five vaccinations were analyzed.Results: Increases in the anti-MAGE-A4-specific antibody response were observed in eight patients (66.7%), compared with six patients (50%) for anti-NY-ESO-1 and five patients (41.7%) for anti-MAGE-A3 after five vaccinations. We identified frequent antigen spreading following MAGE-A4 vaccinations without associations with the clinical response or patient prognosis.Conclusion: Antigen spreading pattern might reflect tumor shrinkage as a response to treatment and treatment history (clinical trial registration number: UMIN000001999).